Maximum Power Point Tracking Using Disturbance Observer-Based Sliding Mode Control for Estimation of Solar Array Voltage. Issue 1 (20th January 2020) - Deshpande, Amruta Sachin; Patil, Sanjaykumar L.; Pandey, Sanjeev Kumar
Abstract: The output power of solar panel in photovoltaic systems is affected by changes in environmental and load conditions. Most currently developed MPPT control algorithms require measurements of panel output voltage, output current, and converter output voltage. In this paper, a new scheme that can cater to uncertainties in the environmental and load condition, is developed using a disturbance observer-based sliding mode control (DOSMC). The proposed DOSMC scheme obviates the need of using a panel output voltage sensor. The proposed scheme does not use a discontinuous control, thereby overcoming the problems of chatter normally associated with the conventional sliding mode control (SMC). The stability is proven in the sense of ultimate boundedness. The proposed scheme is validated by extensive simulation and laboratory experimentation under various scenarios of irradiation, temperature, and load conditions and compared with two existing popular schemes.